RUWATAN JAWA DALAM PERSPEKTIF IMAN KRISTIANI - Ignatius Joko Suyanto (Jurnal Teologi (Journal of Theology), 2014)
In this present age, many people tend to be indifferent toward their local culture. To embrace a contemporary culture, often uncritically, they overlook numerous religious and ethical values of their respective local culture. This has motivated the writer to do a research on Javanese culture particularly Ruwatan. Ruwatan is a long maintained Javanese ritual aimed to keep someone out of bad luck or misfortune. At the heart of Ruwatan, the teaching on creation and salvation are intertwined, which are also fundamental in Christian faith and life. Therefore this article will also discuss the Christian faith in the context of Javanese culture, especially in regard of its teaching on creation and salvation.